Hormonal contraception and HIV acquisition among women: an updated systematic review. Issue 1 (9th January 2020) - Curtis, Kathryn M; Hannaford, Philip C; Rodriguez, Maria Isabel; Chipato, Tsungai; Steyn, Petrus S; Kiarie, James N
Abstract : Objective: To update a 2016 systematic review on hormonal contraception use and HIV acquisition. Methods: We searched Pubmed and Embase between 15 January 2016 and 26 June 2019 for longitudinal studies comparing incident HIV infection among women using a hormonal contraceptive method and either non-users or users of another specific hormonal contraceptive method. We extracted information from newly identified studies, assessed study quality, and updated forest plots and meta-analyses. Results: In addition to 31 previously included studies, five more were identified; three provided higher quality evidence. A randomised clinical trial (RCT) found no statistically significant differences in HIV risk among users of intramuscular depot medroxyprogesterone acetate (DMPA-IM), levonorgestrel implant (LNG implant) or the copper intrauterine device (Cu-IUD). An observational study found no statistically significant differences in HIV risk among women using DMPA, norethisterone enanthate (NET-EN), implants (type not specified) or Cu-IUD. Updated results from a previously included observational study continued to find a statistically significant increased HIV risk with oral contraceptives and DMPA compared with no contraceptive use, and found no association between LNG implant and HIV risk. Conclusions: High-quality RCT data comparing use of DMPA, LNG implant and Cu-IUD does not support previous concerns from observational studies that DMPA-IM use increases the risk of HIV acquisition. Use of other hormonal contraceptive methods (oral contraceptives, NET-EN and implants) is not associated with an increased risk of HIV acquisition.